THE USE OF ENGLISH BORROWING INTO INDONESIAN IN A DAILY NEWSPAPER “RADAR SULTENG” - NFN Herawati (Balai Bahasa Sulawesi Tengah, 2015)
Abstract The roles of language use in printed mass media, especially in a daily newspaper,such as in “Radar Sulteng”, are important enough to have been dominant. Thereare some registers and language variations used in it. This research aims to describe the form of English borrowing into Indonesian and to describe the factorsaffected the use of those loanwords. Borrowing can be defined as the transfer oflinguistic materials from English as the source language (SL) into Indonesia as therecipient language (RL) via the agency of speakers for whom the latter is thelinguistically dominant language. This research focus more on the linguistic andsociolinguistic processes underlying borrowing. The linguistic’s insight attemptedto describe some factors of borrowing, those are: there is no sufficient words in RL(Indonesia); giving semantic’s meaning from SL; giving a specific register in RL byimported materials from SL; and adopting of lexical materials along with someovert structural elements into Indonesia. Meanwhile, from sociolinguisticprocesses, there are two reasons determined borrowing, to indicate the personalidentity and to indicate the concept of modernity.